Agotamiento emocional: un estudio transversal sobre prevalencia de burnout entre profesionales de salud según área de trabajo durante pandemia covid-19, en Pichincha - Ruiz Torres, Gina Margarita (2021)
Worldwide, pandemics not only cause physical alterations in people who contract them, but also have a high psychological impact on health personnel. Currently, working during the Covid-19 pandemic represents a challenge for the mental health of health professionals. Knowledge about their work situation in relation to their area of work and its association with mental health is limited. Therefore, the aim of this study was to evaluate the prevalence of developing Burnout Syndrome associated with working conditions in health personnel according to the area of work (Covid-19 area vs. Non-Covid-19 area) in the province of Pichincha. This cross-sectional study included a convenience sample of 790 health professionals working in the province of Pichincha. Participants were recruited through a brief online questionnaire (Facebook, personal contacts, emails), from February to April 2021. Questions included sociodemographic data, level of studies, occupation, employment and general health conditions, violence in the violence in the workplace, emotional imbalance and burnout. The latter was assessed using the Maslach Burnout Questionnaire. Descriptive statistics were followed by logistic regression analyses adjusted for potential confounders. Approximately a quarter of the population presented risk of developing Burnout (22.28 per cent). 26.9 per cent of health personnel working in Covid-19 area had higher risk of developing Burnout vs. 15.87 per cent in non-Covid-19 area; (p minus 0.01). After adjustment, working in the first line of care (Covid-19 area), (OR19 1.55 CI 95 per cent 1.01-2.37) was statistically significantly associated with the risk of developing Burnout Syndrome. Working directly with Covid-19 patients is common during this pandemic and may result in negative psychological effects on healthcare workers.